La Comunidad Andina en el contexto global posreingeniería de 2014: una mirada desde la acción colectiva (Tema Central) - Piña García, Denny Eryck (2020)
The Andean Community (CAN) is a regional integration bloc and its progress has always been in debate. This essay uses the theoretical tools of the political sciences, specifically the theory of collective action, to analyze the integration process from the 2014 reengineering onwards. The results of the analysis allow to determine that each member gives a different valuation to the identification of the so-called collective assets of the bloc. Under this logic, this assessment has a direct impact on the success of the international organization in the context of a globalization that increasingly requires global results from a governance perspective.